The interaction between dietary fiber and gut microbiota, and its effect on pig intestinal health - Hu, Ruiqi; Li, Shuwei; Diao, Hui; Huang, Chongbo; Yan, Jiayou; Wei, Xiaolan; Zhou, Mengjia; He, Peng; Wang, Tianwei; Fu, Hongsen; Zhong, Chengbo; Mao, Chi; et al. (Frontiers in Immunology, 2023)
Intestinal health is closely associated with overall animal health and performance and, consequently, influences the production efficiency and profit in feed and animal production systems. The gastrointestinal tract (GIT) is the main site of the nutrient digestive process and the largest immune organ in the host, and the gut microbiota colonizing the GIT plays a key role in maintaining intestinal health. Dietary fiber (DF) is a key factor in maintaining normal intestinal function. The biological functioning of DF is mainly achieved by microbial fermentation, which occurs mainly in the distal small and large intestine. Short-chain fatty acids (SCFAs), the main class of microbial fermentation metabolites, are the main energy supply for intestinal cells. SCFAs help to maintain normal intestinal function, induce immunomodulatory effects to prevent inflammation and microbial infection, and are vital for the maintenance of homeostasis. Moreover, because of its distinct characteristics (e.g. solubility), DF is able to alter the composition of the gut microbiota. Therefore, understanding the role that DF plays in modulating gut microbiota, and how it influences intestinal health, is essential. This review gives an overview of DF and its microbial fermentation process, and investigates the effect of DF on the alteration of gut microbiota composition in pigs. The effects of interaction between DF and the gut microbiota, particularly as they relate to SCFA production, on intestinal health are also illustrated.